La Dixième Muse : le Mag' des Filles qui aiment les Filles. (Lille : Les Editions Lydiennes.)
Fonds Suzan Daniel (FSD)
Periodiciteit: tweemaandelijks
Redactie; 128 rue du Faubourg de Douai 59000 Lille
Frans
Periodiek